Needs assessment for behavioral parent training for ADHD in Brazil - Bado, Patricia; da Costa, Raquel; Bernardes, Camila; Tripp, Gail; Mattos, Paulo; Furukawa, Emi (Frontiers in Psychiatry, 2023)
Introduction Attention-Deficit/Hyperactivity Disorder (ADHD) is a debilitating condition affecting children and their families worldwide. Behavioral parent training is a recommended form of empirically supported non-pharmacological intervention for young children with mild to moderate ADHD. However, access to such treatment is limited in many countries. Here we identify the treatment needs of Brazilian families with children demonstrating symptoms of ADHD, and the barriers families face in accessing behavioral treatment. Methods A qualitative needs assessment was undertaken with parents (n = 23), educators (n = 15), and healthcare providers (n = 16). Semi-structured telephone interviews were conducted, and common themes were identified through inductive coding of participants’ responses. Results Participants reported a lack of accessible behavioral treatment, and delays in accessing treatment when available. The majority of parents had not received behavioral parent training, despite it being a recommended form of treatment. Parents, educators and healthcare providers strongly endorsed a need for practical tools to manage the behavior of children with ADHD. Conclusion Existing services might not meet the needs of children with ADHD and their families in Brazil. Easily accessed behavioral parent training programs are recommended to address the identified treatment gap for Brazilian children with ADHD and their families.